The objective of psychology -II- The psychic facts and the object of psychology - Santibañez-H., Guy; Osorio H., Hector (Revista de Psicología, 1999)
The first part of this study, published in the previous issue of this journal (Vol. VII 1988), reviewed the evolution of the object of our science, within the ambit of the greco-latin culture. In this paper we present arguments related to the fundamental properties of psychological phenomenae; we describe their five characteristics, as well as the characterization of the adaptation process as a fundamental elment in the real knowledge of the object of Psychology, wich should lead to wider and greater debate on the problem. The main objetive of our presentation is to liberate the psychological sciences from a series of prejuices and half truths derived from philosophy, theology and scholastics. These have been the cause of misunderstanding among the different streams of opinion or schools that are dedicated to understan only those sectors that form part of their study object.